The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1995
DOI: 10.1161/01.res.77.1.64
|View full text |Cite
|
Sign up to set email alerts
|

Localization of Atrial Natriuretic Factor Receptors in the Mesenteric Arterial Bed

Abstract: Although receptors for atrial natriuretic factor (ANF) and angiotensin II (Ang II) have been reported in rat mesenteric arteries, both peptides induce weak biological responses. Endothelin-1 (ET-1) evokes a potent vasoconstriction in the mesenteric artery. To identify the tissue localization of ANF, Ang II, and ET-1 receptors, radioligand binding experiments with 125I-ANF, 125I-[Sar1,Ile8]Ang II, and 125I-ET-1 were performed in defatted mesenteric arteries and in the surrounding adipose tissue. 125I-ANF bindin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…Other authors have shown the presence of abundant clearance receptor binding and protein in adipocytes. 18,19,22 Moreover, plasma levels of ANP in obese hypertensives were found to be lower than those measured in obese normotensive individuals, together with higher gene expression of the clearance receptor for NP in adipose tissue. 24 These findings are consistent with the hypothesis that the increased total adipose mass of obese hypertensives, through the enhanced expression of the biologically inactive NPr-C, 14,15 might influence the activity of NP.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Other authors have shown the presence of abundant clearance receptor binding and protein in adipocytes. 18,19,22 Moreover, plasma levels of ANP in obese hypertensives were found to be lower than those measured in obese normotensive individuals, together with higher gene expression of the clearance receptor for NP in adipose tissue. 24 These findings are consistent with the hypothesis that the increased total adipose mass of obese hypertensives, through the enhanced expression of the biologically inactive NPr-C, 14,15 might influence the activity of NP.…”
Section: Discussionmentioning
confidence: 93%
“…20,21 Other authors have shown the presence of abundant clearance receptor binding and protein in adipocytes. 22 Moreover, in adipose tissue NPr-C expression is dramatically inhibited by fasting, indicating a nutritional regulation of this receptor. 23 Plasma levels of ANP lower than that found in obese normotensive individuals have been shown in obese hypertensives, together with higher gene expression of the clearance receptor for NP in the adipose tissue.…”
mentioning
confidence: 99%
“…NPR-A have also been identified in rat fat cells. 78,79 A weak ANP-stimulated increment of cGMP was reported in rat fat cells. 80 Human adipose tissue expresses NPR-A and NPR-C messenger RNA.…”
Section: Natriuretic Peptide Receptorsmentioning
confidence: 98%
“…The affinity of all three peptides for the clearance receptor is similar (Koller et al, 1991;Suga et al, 1992). The distribution of the NP receptors varies among tissues (De Leon et al, 1995;Dos Reis et al, 1995). It appears to be transcriptionally regulated at different development stages (Brown and Chen, 1995) and in different physiological or pathological states (Yoshimoto et al, 1996), thus dictating the effects of the different NPs on a specific tissue.…”
Section: Guanylate Cyclasesmentioning
confidence: 99%